Poly(2-(dimethylamino) ethyl methacrylate)-b-poly(lauryl methacrylate)-b-poly(oligo ethylene glycol methacrylate) triblock terpolymer micelles as drug delivery carriers for curcumin - Skandalis,A; Selianitis,D; Sory,DR; Rankin,SM; Jones,JR; Pispas,S (Journal of Applied Polymer Science, 2022)
This work aims to investigate the ability of poly[2-(dimethylamino)ethyl methacrylate-b-lauryl methacrylate-b-(oligo ethylene glycol)methacrylate], PDMAEMA-b-PLMA-b-POEGMA amphiphilic triblock terpolymers, to encapsulate the model hydrophobic compound curcumin. The terpolymers were synthesized by RAFT polymerization methodologies at variable molecular weights and compositions and self-assemble into spherical micelles with mixed PDMAEMA/POEGMA coronas and PLMA cores, when inserted in aqueous solutions. Fourier transform infrared and UV–Vis spectroscopy measurements were utilized in order to confirm and quantify the encapsulation of curcumin within the polymeric micelles respectively. Dynamic light scattering was used for the investigation of the size of the nanostructures formed and transmission electron microscopy proved that their morphology is spherical. Moreover, the colloidal stability of the systems in physiological conditions was assessed and two independent in vitro cytotoxicity assays revealed that curcumin-loaded PDMAEMA-b-PLMA-b-POEGMA micelles were not cytotoxic.